Efektivitas Bimbingan Konseling: Studi Kasus Konselor di SMAN 3 Karawang - Muthia Hanifa Nugraha Muthia; Mimah Mahmudah; Irfan Nawawi; Muhajir A.M Al Raaji; Nur Aini Farida (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
Counseling is an essential service for helping students overcome academic and non-academic challenges and preparing them for future challenges. This study aims to assess the effectiveness of counseling services at SMAN 3 Karawang, focusing on the role of counselors in providing individual and group counseling services, as well as counseling activities. Furthermore, it explores factors influencing the success of counseling services, such as school support and student participation in the program. Through interviews with counselors, observations of service implementation, and documentation of counseling activities, the results indicate that the effectiveness of counseling in schools is strongly influenced by active student involvement and counselor competence in delivering materials. Optimal counseling services can improve students' psychological well-being, social skills, and academic achievement. Thus, this study emphasizes the importance of counseling as an integral part of holistic education.